Field reports form for submitting seasonal observations of Iowa birds, Carolyn J. Fischer, fall 1992 - Fischer, Carolyn J.et al (1992)
Fall reports of birds found in Cerro Gordo County contributed by Carolyn J. Fischer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed